Tradisi Pesantren Salafiyah dan Modern dalam Konteks Deradikalisasi - M. Kholid Thohiri (Proceedings of Annual Conference for Muslim Scholars, 2018)
Religious radicalism is associated with pondok pesantren, there are at least two main features of radical pesantren. First, these pesantrens are generally "imported" from the country that became the basis of radical Islam. secondly, his textualistic- scriptistic style in Thought, on the other, most of the actors of radicalism and terrorism on behalf of; Islam in Indonesia is alumni of madrasah education or pesantren. In the context of this research is researchers try to find strategies and efforts Pondok pesantren in order to prevent radicalization in Pondok Pesantren, in order to prevent radicalization in Pondok Pesantren, especially in pondok pesantren Salafiyyah Panggung and Pondok pesantren Modern Tawangsari Tulungagung. This study aims to reveal the construction of radicalism according to the pesantren community. then reveals the tradition and role of pesantren in the context of deradicalization. This research uses qualitative research methods with data collection methods through interviews, observation and documentation in the two Pondok Pesantren. While data analization using multi case study and validity testing of data use triangulation and extended participation. The result of this research is the view of the pesantren community against Islamic radicalism. First, Islamic radicalism is a notion that has an intolerant characteristic of plurality. Second, the way of understanding the superficial and literalist religion, is the factor causing people to be radical in understanding the teachings of Islam even in action. Thirdly, the radical movement not only threatens ukhuwwah islamiyyah, but also threatening the nation's brotherhood of Indonesia. Fourth, pondok pesantren is part of Islamic educational institutions that carry moderate Islam in Indonesia. fifth, the idea of radicalism is not in accordance with the teachings of Islam. While the Tradition of Pesantren in the context of deradicalization, firstly, through a curriculum whose contents make students who understand and explore the religion of Islam through the teaching of the book that has a plurality of interpretation and comparison of schools especially in Islamic law. Secondly, the tradition of scholarship in pondok pesantren in the context of preventing radicalization is supported by a learning model that develops a critical and tolerant attitude through the pondok pesantren program. Third, in the pondok pesantren develops multicultural education through a happy stage activity featuring santri creativity in art and culture and ethnic Nuusantara.